Development of Scientific-Based Student Worksheets (LKPD) Using the Discovery Learning Model to Improve Science Skills of Sixth Grade Elementary Students - Efa Rosalina Sitorus; Ely Djulia; Sumarno (South Sulawesi Education Development (SSED), 2025)
This research aims to describe: Validity and practicality of scientific-based LKPD using the Discovery Learning model. This research is development research using the ADDIE model which was carried out in class VI of SDN 173662. The research results obtained are: The module developed has been categorized as Valid, Practical and Effective. Based on the validation results of the material expert, the category was